Mathematics Curriculum Review by Advancing the Use of Learning Design Map and Subjects Classification - Fathurrohman, Maman; Porter, Anne; Worthy, Annette; Abdullah, Rosni; Supriyanto, Supriyanto; Pamungkas, Aan Subhan (International Journal on Emerging Mathematics Education, 2019)
Curriculum review is a long process. Typically, the people responsible for these activities are one or two people (coordinators) who are responsible for this and it can be burdensome. Authors propose a new computer-based method for mathematics curriculum review by advancing the use of Learning Designs Maps (LDMaps). The LDMaps have already been developed by authors to document expected mathematics teaching and learning experiences as expected by curriculum. The proposed method can disperse the process allowing the responsible coordinators to conduct the simple task of collating available LDMaps for the review. In this paper, an example of mathematics curriculum review in counting mathematics subjects classification entries is presented.